2012
DOI: 10.1007/s11192-012-0890-7
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of collaboration and its relationship with research impact in a biomedical field

Abstract: This paper analyses existing trends in the collaborative structure of the Pharmacology and Pharmacy field in Spain and explores its relationship with research impact. The evolution in terms of size of the research community, the typology of collaborative links (national, international) and the scope of the collaboration (size of links, type of partners) are studied by means of different measures based on co-authorship. Growing heterogeneity of collaboration and impact of research are observed over the years. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 39 publications
(30 reference statements)
2
26
0
2
Order By: Relevance
“…Different indicators have been introduced to quantify collaboration in research papers (see for example, Egghe, 1991;Glänzel & Schubert, 2004;Vinkler, 2010) and extensive literature has been devoted to explore collaboration patterns (Bordons & Gómez, 2000) and the influence of collaboration on the productivity of scientists and on the impact of research (Abramo, D'Angelo, & Di Costa, 2009;Bordons, Aparicio, & Costas, 2013;Glänzel, 2001;Lee & Bozeman, 2005). In most recent years, the application of social network analysis to study co-authorship relations has emerged as an interesting approach, since it allows us to visualise and investigate social structures and relations (see for example, Abbasi, Altmann, & Hossain, 2011;Abbasi, Chung, & Hossain, 2012;Jansen, von Görtz, & Heidler, 2010;Li-Chun, Kretschmer, Hanneman, & Ze-Yuan, 2006;Newman, 2001;Otte & Rousseau, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Different indicators have been introduced to quantify collaboration in research papers (see for example, Egghe, 1991;Glänzel & Schubert, 2004;Vinkler, 2010) and extensive literature has been devoted to explore collaboration patterns (Bordons & Gómez, 2000) and the influence of collaboration on the productivity of scientists and on the impact of research (Abramo, D'Angelo, & Di Costa, 2009;Bordons, Aparicio, & Costas, 2013;Glänzel, 2001;Lee & Bozeman, 2005). In most recent years, the application of social network analysis to study co-authorship relations has emerged as an interesting approach, since it allows us to visualise and investigate social structures and relations (see for example, Abbasi, Altmann, & Hossain, 2011;Abbasi, Chung, & Hossain, 2012;Jansen, von Görtz, & Heidler, 2010;Li-Chun, Kretschmer, Hanneman, & Ze-Yuan, 2006;Newman, 2001;Otte & Rousseau, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, collaboration networks are an important medium for examining scholarly communication [22]. Some scholars investigated the networks as well as core groups of international collaboration in either specific fields or selected cooperating partners at the country and institution levels [23][24][25][26][27]. Country-level collaboration studies help in the examination of the roles of every nation, while institution-level collaboration studies are useful for exploring the typology of collaborative links (national and international), the size of the research community, and the scope of the collaboration.…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%
“…Although co-authorship is not the only trace collaboration leaves, studies in this regard have shown that it enhances research productivity (Lee & Bozeman, 2005) and citation impact (Glänzel, 2001). Other studies suggest further benefits when such collaboration is between authors from different institutional categories, such as more innovative and creative research (Bordons, Aparicio, & Costas, 2013). In this context, it is not surprising the introduction of research policies and strategies to promote such collaboration links in the biomedical sciences.…”
Section: Introductionmentioning
confidence: 99%